Strategic cooperation through takmil wal istikmal among Islamic private schools in Malaysia - Yahya, Rohaziah; Mhd. Sarif, Suhaimi (2019)
In the fast moving world, there is growing preference among parents to send their children to Islamic Private Schools, particularly Islamic schools with integrated curriculum. Even though education matters still under the purview of the Ministry of Education, Islamic Private Schools do not enjoy similar services and benefits in terms of training, exchange of resources and professional development. This situation has motivated strategic cooperation among Islamic Private Schools to share resources and professional development on win-win situation. This study aims to explore the influence of takmil wal istikmal (reciprocal perfecting) among Islamic Private Schools. This study uses personal interview with headmasters of Islamic Private Schools in Selangor. The preliminary results showed that takmil wal istikmal occurs at minimal level in a few areas, namely sharing of curriculum development, exchange of examination papers, sharing of teaching training, and student development. The main reason for the minimal reciprocal perfecting collaboration is due to individual school governance preference. The informants suggest for formalization of the strategic cooperation through formal council or entity at the Ministry of Education through the private school department.